Risk factors and vaccination gaps for herpes zoster in people living with HIV: A multicenter multivariable study - Akca, Veysel; Akbulut, Ilkay; Yilmaz, Gul Ruhsar; Kayaaslan, Bircan; Eser, Fatma; Baygunes, Setenay Nisa; Togan, Turhan (Sage Publications Ltd, 2026)
Purpose: The primary aim of this study was to determine the frequency of prior herpes zoster and its associated clinical and immunovirological factors, while secondary aims included evaluating varicella-zoster virus serostatus and vaccination rates. Methods: In this multicenter, retrospective, and partially observational study, data from 1,289 people living with HIV between January 2020 and December 2024 were analyzed. Attitudes toward vaccination were also examined. Results: A history of herpes zoster was identified in 5% of participants (n = 65). Individuals with an herpes zoster history were significantly older than those without (45.5 +/- 13.1 vs 38.1 +/- 12.9 years; p < 0.001). Herpes zoster history was strongly associated with advanced disease stage at diagnosis (p < 0.001), lower CD4 percentages (p = 0.020), reduced absolute CD4 counts (p < 0.001), and lower CD4/CD8 ratios (p = 0.006) in univariate analysis.Other factors significantly associated with herpes zoster history included prior viremia (p < 0.001), chronic lung disease (p = 0.006), syphilis (p = 0.016), hepatitis B virus coinfection (p < 0.001), malignancy (p < 0.001), and immunomodulatory drug use (p = 0.031). Lack of childhood varicella vaccination was also significantly associated with herpes zoster history (p = 0.003). In multivariable logistic regression analysis, lower CD4 count (aOR 0.992; p = 0.001), history of viremia (aOR 5.74; p = 0.004), malignancy (aOR 8.51; p = 0.007), and hepatitis B virus coinfection (aOR 23.56; p = 0.002) were independently associated with herpes zoster. herpes zoster-related pain was reported in 24 patients (36.9%) and was most frequently treated with non-steroidal anti-inflammatory drugs. Herpes zoster vaccination coverage was notably low, and willingness to be vaccinated remained similarly limited in both groups. Conclusion: Herpes zoster history among people living with HIV was associated with older age, advanced immunosuppression, viremia, and comorbidities, particularly hepatitis B virus and syphilis. Despite the considerable burden of herpes zoster and its complications, vaccination rates remain low. These findings highlight the need to identify high-risk groups and implement targeted vaccination strategies to reduce herpes zoster-related morbidity among people living with HIV.
Keywords: immunization; HIV; herpes zoster; varicella-zoster virus; coinfection; vaccination uptake